Real-world evidence on perioperative chemotherapy in localized soft tissue sarcoma of the extremities and trunk wall; a population-based study. (3rd July 2022) - Boye, Kjetil; Lobmaier, Ingvild; Kobbeltvedt, Marthe Rosvoll; Thorkildsen, Joachim; Taksdal, Ingeborg; Bjerkehagen, Bodil; Bruland, Øyvind S.; Zaikova, Olga; Sundby Hall, Kirsten; Hompland, Ivar
Abstract: Background: Data from the real-world setting on perioperative chemotherapy in high-risk, localized soft tissue sarcoma (STS) is limited. Real-world data (RWD) includes data derived from patients treated outside clinical trials and often captures long-term follow-up not recorded in clinical trials. The aim of this study was to provide population-based, real-world evidence on perioperative chemotherapy in localized STS. Material and methods: Adult patients with localized STS in the extremities or trunk wall treated at Oslo University Hospital, Oslo, Norway from 1998 to 2017 were included in the study. Data were extracted from a prospectively maintained database, supplemented by retrospective review of medical records. Results: The total study cohort included 806 patients, of whom 154 (19%) received perioperative chemotherapy. A regimen with anthracycline and ifosfamide was given in 141 of 154 cases (92%). During long-term follow-up two patients developed secondary malignancies, cardiac toxicity was registered in 11 patients (7%) and renal toxicity in 12 patients (8%). Seventy-one of 154 patients (46%) were treated outside of clinical trials and constituted the RWD cohort. The median age at surgery was slightly lower and there were more synovial sarcomas and fewer myxofibrosarcomas in the RWD cohort. No difference in chemotherapy dose intensity was observed. The estimated 5-year metastasis-free survival (MFS) in all patients receiving perioperative chemotherapy was 58%. In the RWD cohort 5-year MFS was 53% and in the clinical study cohort 61% (HR 1.24; 95% CI 0.77–2.00). Conclusion: Long-term outcome after perioperative chemotherapy was comparable for patients treated in routine clinical practice to those in clinical trials. Secondary malignancy and cardiac toxicity were observed. The risk of serious late side effects should be included in the decision process on perioperative chemotherapy.